Binge drinking - Hayward, Nick; Garner, Simon; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2004)
This program explores issues with young people and alcoholic binge drinking. It describes what binge drinking is, who is likely to be involved in bringe drinking, and the effects and consequences of this behaviour
Title from title screen
Executive producer, Mark McAuliffe ; editor, Nick Hayward ; sound, Wayne Martin ; camera, Richard Leigh, Simon Garner, Nick Phelps
Voice over: Glen Hancox
Keywords: Alcoholism; Binge drinking; Alcoholism and crime